Moderation of Islamic Business Ethics to The Personality of Business Behavior - Susriyanti Susriyanti; Sitti Rizki Mulyani; Fitri Yeni (Quantitative Economics and Management Studies, 2022)
The purpose of the study was to study whether moderation of Islamic business ethics can increase the influence of personality on the business behavior of Bengkoang sellers. This study was a field study in Padang City, with 101 samples of bengkoang sellers. Data collection techniques are observation, survey, and questionnaire and data processing with SPSS 25. Validity test, CFA Test. Hypothesis testing using MRA (Moderating Regression Analysis). This study produced the equation of the regression test results between Islamic Business Ethics, and Trader Behavior is Y = 21.689 + 0.419X1 + e, where the constant value indicates if Islamic Business Ethics does not exist, then Trader Behavior will still be formed as much as the existing constant value of 21,689. The application of Islamic Business Ethics to the behavior of bengkoang sellers in the city of Padang plays a positive and significant role.